“PENGARUH MANAJEMEN LABA DAN KUALITAS AUDIT TERHADAP BIAYA MODAL EKUITASPADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PERIODE PENGAMATAN DARI TAHUN 2014 SAMPAI 2016” - Frisnanto Bagas Lazuardi, 14.05.52.0145; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the effect of earnings management, and audit quality on cost of equity capital. Earnings management proxy using Spesific Accrual, audit quality proxy using dummy variable is the value of 1 for Big Four KAP and value 0 for Non Big Four KAP, and cost of equity capital is estimated by Ohlson model. This study sampled manufacturing companies of consumption goods industry listed in Indonesia Stock Exchange during 2014-2016. This data to obtainable with purposive sampling and uses double regression analyze method. Based on double regression analyze method, the result of this research show that earning management has a positive and significant effect the cost of equity capital. Audit quality does not effect the cost of equity capital. Laverage does not effect the cost of equity capital, and Firm size has a negative and significant effect the cost of equity capital. Keyword : Earnings Management, Audit Quality, Cost of Equity Capital, Leverage, Size.